2006
DOI: 10.1093/aje/kwj224
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Randomized Trial Evaluating the Clinical and Economic Effectiveness of Acupuncture for Chronic Low Back Pain

Abstract: In a randomized controlled trial plus a nonrandomized cohort, the authors investigated the effectiveness and costs of acupuncture in addition to routine care in the treatment of chronic low back pain and assessed whether the effects of acupuncture differed in randomized and nonrandomized patients. In 2001, German patients with chronic low back pain were allocated to an acupuncture group or a no-acupuncture control group. Persons who did not consent to randomization were included in a nonrandomized acupuncture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
231
1
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(249 citation statements)
references
References 27 publications
3
231
1
14
Order By: Relevance
“…The majority of trials examined in this systematic review were already included in the 2005 Cochrane systematic review update; however, Ammendolia et al contributed three novel trials of interest. 30,31,32 26 Yuan and colleagues were in accordance with Ammendolia et al, concluding that acupuncture did not differ from sham in pain reduction or functional improvement. They also affirmed previous findings that acupuncture is more effective than no treatment at all, and that acupuncture improves outcomes as an adjunct to other therapy.…”
Section: Resultssupporting
confidence: 64%
“…The majority of trials examined in this systematic review were already included in the 2005 Cochrane systematic review update; however, Ammendolia et al contributed three novel trials of interest. 30,31,32 26 Yuan and colleagues were in accordance with Ammendolia et al, concluding that acupuncture did not differ from sham in pain reduction or functional improvement. They also affirmed previous findings that acupuncture is more effective than no treatment at all, and that acupuncture improves outcomes as an adjunct to other therapy.…”
Section: Resultssupporting
confidence: 64%
“…The size of both of these studies was based on finding a main treatment effect rather than a moderation of such an effect. To our knowledge, only 1 trial has been explicitly powered to show moderator effects (n ϭ 3,093) (28). In that trial, Witt et al found that acupuncture was more effective for those with worse initial back function, younger patients, and those with Ͼ10 years of schooling (28).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 1 trial has been explicitly powered to show moderator effects (n ϭ 3,093) (28). In that trial, Witt et al found that acupuncture was more effective for those with worse initial back function, younger patients, and those with Ͼ10 years of schooling (28). Although we consider we have used the most appropriate statistical approach to our data, this approach may not yield positive results unless there are resources to run more trials of a similar size to the acupuncture trial by Witt et al It is, therefore, perhaps surprising that some other studies have found apparently important effects on much smaller numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Witt et al 8 realizaram um estudo clínico randomizado e controlado (acupuntura versus grupo controle), com um braço de coorte não-randomizado e prospectivo, onde pacientes negaram-se a ser alocados para o grupo controle para avaliar o custoefetividade de acupuntura no tratamento de dor lombar baixa. Todos os grupos receberam medicação consagrada para dor lombar.…”
Section: Prática Baseada Em Evidênciasunclassified